"The Only Thing That's Real Is Me": CM Punk and the Rhetorical Framework of the American Dream. Issue 4 (7th August 2020) - Key, Adam
ABSTRACT: Although the world of professional wrestling is characterized as larger than life, a speech by World Wrestling Entertainment (WWE) wrestler Phillip Brooks appeared to cross the line between fantasy and reality. Brooks' speech, instead of being character driven, focused on his lack of promotion despite his tenure of hard work. He broke character, addressing specific elements of backstage politics which affected his actual self rather than the character he portrays, CM Punk. The speech makes apparent the pieces of the previously shrouded oppressive WWE machine. The text is rhetorically examined from the perspective of mythological criticism. Analysis revealed that the speech is an enactment of the myth of the American Dream, where Brooks plays the role of the American Adam. Brooks' Adam, however, is not the idealistic sprite typical of Horatio Alger's work, but a darker Adam who has experienced the Fall. Brooks' speech provides a basis for the expansion of the myth as an exhortation for the oppressed to speak up in order to achieve their own American Dreams.